ON THE IMPORTANCE OF PHRASEOLOGICAL UNITS IN THE FORMATION OF CULTURAL COMPETENCIES IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE (CAHIERS MAGELLANES-NS, 2024)
The article examines the importance of phraseological units in teaching Russian as a foreign language, their role in the formation of cultural competencies. Phraseological units, being part of the linguistic picture of the world, carry a deep cultural meaning, reflecting the peculiarities of the Russian-speaking mentality. They allow foreign students to immerse themselves in the cultural context and gain a deeper understanding of national traditions and worldview. The author emphasizes that successful mastery of phraseological units contributes to intercultural communication and improves the level of proficiency in the Russian language.